Product Quality Analysis as a Tool for Marketing Strategy Planning for Nutmeg Juice Products (Case Study in Bogor City) - Gemina, Dwi; Kartini, Tini; Haris, Helmi; Nurjanah, Dewi Astri (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyse the level of performance and importance of product quality in order to design a marketing strategy for Nutmeg Juice Products. The research population consists of consumers of nutmeg juice products, with a sample size of 75 respondents. This study uses Importance Performance Analysis (IPA). The results of the study show that consumer expectations of nutmeg juice products focus on the uniqueness of the logo, attractive product appearance, and the accuracy of the flavour description on the packaging. Meanwhile, consumers perceive the product performance to be good in terms of ease of storage, health benefits, and long shelf life. Based on IPA analysis, it was found that the three product quality indicators that are the top priorities for improvement are performance, reliability, and quality of conformance. These three indicators are considered very important by consumers, but their performance still does not meet expectations. To achieve an effective marketing strategy, manufacturers can make efforts to improve ease of maintenance, product uniqueness, and aesthetics.